Pengaruh Due Professional Care, Skeptisisme Profesional, Independensi dan Audit Tenure Terhadap Kualitas Audit pada KAP di Kota Denpasar - Ni Made Veny Sukmayanti; I Gusti Ngurah Sanjaya; L. G. P Sri Eka Jayanti (Jurnal Riset Akuntansi Warmadewa, 2020)
The purpose of this study is to empirically prove the influence of due professional care on audit quality, to empirically prove the effect of skeptisisme professional on audit quality, to empirically prove the effect of independensi on audit quality, to empirically prove the effect of audit tenure on audit quality at KAP in Denpasar City. The sampling method used in this study was random sampling. The sample used in the study was 42 respondents from a total population of 9 KAP with 56 auditors. Data collection method used is a questionnaire method that uses a 5-point linkert scale. The analysis technique used is multiple linear analysis. due professional care, skeptisisme professional, independensi, and audit tenure has a positive effect on audit quality at KAP in Denpasar City.